A Review: Development of Transdermal Drug Delivery System By Using Different Modified Chitosan - Main, Pankaj (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTToday about 74% of drugs are taken orally and are found not to be as effective as desired hence, the transdermal drug delivery system has numerous advantages over the more traditional drug delivery route. This includes high bioavailability, absence of first pass hepatic metabolism effect, steady drug plasma concentration, and the fact that therapy is non-invasive. A Transdermal Patch is an adhesive patch that has a coating of medicine (drug) that is placed on the skin to deliver specific dose of the medicine (drug) into the bloodstream over a period of time. This review will give an introduction about the transdermal drug delivery by using modified Chitosan. Chitosan is deacetylated product formed by treatment of chitin with concentrated (50%) caustic alkali. Modified chitosan used as a permeation polymers for biomedical and pharmaceutical application. A thorough understanding of skin physiology and the basics behind the new technologies would be useful for understanding these exciting new drug delivery systems